Recognition of similar epitopes on varicella-zoster virus gpI and gpIV by monoclonal antibodies. - Vafai, A (1988)
Two monoclonal antibodies, MAb43.2 and MAb79.0, prepared against varicella-zoster virus (VZV) proteins were selected to analyze VZV gpIV and gpI, respectively. MAb43.2 reacted only with cytoplasmic antigens, whereas MAb79.0 recognized both cytoplasmic and membrane antigens in VZV-infected cells. Immunoprecipitation of in vitro translation products with MAb43.2 revealed only proteins encoded by the gpIV gene, whereas MAb79.0 precipitated proteins encoded by the gpIV and gpI genes. Pulse-chase analysis followed by immunoprecipitation of VZV-infected cells indicated reactivity of MAb43.2 with three phosphorylated precursor species of gpIV and reactivity of MAb79.0 with the precursor and mature forms of gpI and gpIV. These results indicated that (i) MAb43.2 and MAb79.0 recognize different epitopes on VZV gpIV, (ii) glycosylation of gpIV ablates recognition by MAb43.2, and (iii) gpIV is phosphorylated. To map the binding site of MAb79.0 on gpI, the pGEM transcription vector, containing the coding region of the gpI gene, was linearized, and three truncated gpI DNA fragments were generated. RNA was transcribed from each truncated fragment by using SP6 RNA polymerase, translated in vitro in a rabbit reticulocyte lysate, and immunoprecipitated with MAb79.0 and human sera. The results revealed the existence of an antibody-binding site within 14 amino acid residues located between residues 109 to 123 on the predicted amino acid sequences of gpI. From the predicted amino acid sequences, 14 residues on gpI (residues 107 to 121) displayed a degree of similarity (36%) to two regions (residues 55 to 69 and 245 to 259) of gp IV. Such similarities may account for the binding of MAb79.0 to both VZV gpI and gpIV.